Improving pediatric Inflammatory Bowel Disease (IBD) follow-up. Issue 1 (17th August 2016) - Dykes, Dana; Williams, Elizabeth; Margolis, Peter; Ruschman, Jennifer; Bick, Julianne; Saeed, Shehzad; Opipari, Lisa
Abstract : Standardization of Inflammatory Bowel Disease (IBD) care through participation in the ImproveCareNow (ICN) Network has improved outcomes for pediatric patients with IBD, but under the current care model, our improvements have plateaued. Current ICN model care guidelines recommend health supervision visits every six months. We identified a gap in our practice's ability to ensure either a routine six month follow-up or a rapid follow-up after a disease flare, and a significant number of patients with active disease status during a six month period lacked timely reassessment after interventions or medication changes. Telemedicine provides an alternative method of care delivery to address these gaps, but has had limited use in patients with IBD. A multi-step approach to offer alternative follow-up care options via telemedicine was developed with potential impact on remission rates and quality of life. Short term goals of the pilot were to improve telemedicine access for patients with IBD were to 1) increase the percent of patients with active disease with a follow-up completed within two months of a visit from 40% to 70%, 2) increase the percent of patients with a visit scheduled within two months of their last sick visit from 20% to 70% (interim measure), 3) increase the number of eVisits from zero visits per month to two visits per month during pilot phase, 4) increase electronic communication with patients from zero messages per month to 200 messages per month, 5) no change in complications or adverse events (defined as an unplanned visit or ED (emergency department) encounter within 30 days of an eVisit. The expected outcomes of the e-visit model were to: maintain baseline care standards and health screening capabilities, improve access to care, and provide equivalent care delivery (no increase in the number of unplanned clinical encounters). Using the IHI model for improvement (Plan-Do-Study-Act) we have seen a progressive increase in the rate of patient signups for the electronic medical record patient portal, with a baseline median of 20% per clinic compared with a current median of approximately 70% after six months. We successfully implemented e-messaging in its pilot form among five providers and have seen steady uptake in patient use from 5 patient initiated messages during the first month to 76 messages/month over the past three months. E-visits have replaced a total of 32 visits to date. Medications, nutrition, and disease activity were appropriately screened and managed electronically without the need for a physical office visit by the treating gastroenterologist. Access to care was improved in that all patients completed their e-visits from their homes without missing school or work and did not require a physical office visit. One visit successfully identified worsening of the patient's clinical course and resulted in a scheduled office visit request, but no unplanned office visits or ED visits have occurred. This report represents the first description of telemedicine use in routine clinical care in children with IBD. We anticipate continuing use of this novel mode of health care delivery in pediatrics in an effort to increase the proportion of patients seen for interval follow-up, after IBD diagnosis, or mild flare in an effort to target early treatment changes that should result in improved remission and patient reported outcomes. E-visits are less expensive and time consuming than traditional visits and may serve as an additional method of cost savings by matching care to a patient's individual needs.